Front Cover: Salted and Unsalted Zhàcài (Brassica juncea var. tumida) Alleviated High‐Fat Diet‐Induced Dyslipidemia by Regulating Gut Microbiota: A Multiomics Study. Issue 24 (17th December 2020) - Li, Wenfeng; Chen, Chunlian; Chen, Mengting; Zhang, Xiangyang; Ji, Qin; Wang, Yu; Zheng, Qiaoran; Tan, Si; Gao, Xiaoxv; Lu, Yalong
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000798 DOI: 10.1002/mnfr.202000798 Zhàcài, a salting‐processed Brassica juncea var. tumida vegetable, is widely consumed as a pickle. The results of multiomics study suggest that consumption of salted and unsalted Zhàcài may effectively prevent high‐fat‐induced dyslipidemia by regulating gut microbiota. Moverover, the anti‐dyslipidemia effect of unsalted Zhàcài is stronger than that of salted Zhàcài. This is reported by Wenfeng Li, Chunlian Chen, Mengting Chen, Xiangyang Zhang, Qin Ji, Yu Wang, Qiaoran Zheng, Si Tan, Xiaoxv Gao, Yalong Lu in article 2000798 .